Successful detection of an incidental sigmoid injury during laparoscopic surgery by air saline test in a patient of endometrial carcinoma - Sharma, Pooja; Mishra, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Laparoscopy has many advantages over open surgery including less post-operative pain, earlier return of normal bowel function, shorter hospital stay, and earlier recovery. Bowel injury is a serious complication of gynecological laparoscopy. The most common site of bowel injury is the small bowel, followed by the large bowel and stomach. This is in agreement with a recent systematic review which has shown that the incidence of bowel injury in gynecologic laparoscopy is 1 in 769.3. Air saline test performed to check bowel integrity by inserting the rectal probe and filling the cavity with normal saline. After performing total laparoscopic hysterectomy with bilateral salphingoopherectomy with retroperitoneal lymphnode dissection done initially after pushing air from rectal probe into the bowel, no bubble was noted but after pushing sigmoid into the pool of saline, escape of air was seen. After suction, a 2×2 cm incidental sigmoidal injury was detected. Bowel injury is a serious complication in laparoscopic surgeries and routine intraoperative checking of bowel integrity by air saline test with the help of rectal probe is a useful modality of intraoperative bowel repair.